Downstaging prior to liver transplantation for hepatocellular carcinoma: advisable but at the price of an increased risk of cancer recurrence – a retrospective study. (10th September 2018) - Toso, Christian; Meeberg, Glenda; Andres, Axel; Shore, Carolina; Saunders, Colleen; Bigam, David L.; Shapiro, Andrew Mark James; Compagnon, Philippe; Berney, Thierry; Majno, Pietro; Kneteman, Norman
Summary: The use of downstaging prior to liver transplantation for hepatocellular carcinoma (HCC) still needs refinement. This study included patients with HCC listed for transplantation according to the Total Tumour Volume (TTV) ≤115 cm 3 and alpha fetoprotein (AFP) ≤400 ng/ml criteria, with and without previous downstaging. Overall, 455 patients were listed, and 286 transplanted. Post‐transplant follow‐up was 38.5 ± 1.7 months. Patients downstaged to TTV115/AFP400 ( n = 29) demonstrated similar disease‐free survivals (DFS, 74% vs. 80% at 5 years, P = 0.949), but a trend to more recurrences (14% vs. 5.8%, P = 0.10) than those always within TTV115/AFP400 ( n = 257). Similarly, patients downstaged to Milan criteria ( n = 80) demonstrated similar DFS (76% vs. 86% at 5 years, P = 0.258), but more recurrences (11% vs. 1.7%, P = 0.001) than those always within Milan ( n = 177). Among patients downstaged to Milan, those originally beyond TTV115/AFP400 ( n = 27) had similar outcomes as those originally beyond Milan, but within TTV115/AFP400 ( n = 53). However, the likelihood of being within Milan at transplant was lower for patients with more advanced original HCCs ( P < 0.0001). Overall, despite an expected increase in post‐transplant HCC recurrence, similar survivals can be achieved with and without downstaging, using the TTV115/AFP400 transplantation criteria, and including patients with advanced original HCCs. Downstaging should continue to be performed.